A Textual Amulet from Theban Tomb 313 (Papyrus MMA 26.3.225) - Dieleman, Jacco.
Edition of a textual amulet held in The Metropolitan Museum of Art in New York (MMA 26.3.225). Found in Theban Tomb 313 as a folded and tied packet, the papyrus sheet is inscribed with an apotropaic incantation and drawing. The incantation invokes “The Entities of Khemenu,” that is, the eight members of the Ogdoad, and orders them to offer protection to the owner of the amulet. The drawing is only partly preserved, but depicted originally two symmetrically arranged crocodiles attacking a figure positioned between them.  doi: http://dx.doi.org/10.5913/jarce.53.2017.a012